2023
DOI: 10.1111/anae.15987
|View full text |Cite
|
Sign up to set email alerts
|

A national cohort study to investigate the association between ethnicity and the provision of care in obstetric anaesthesia in England between 2011 and 2021

Abstract: There is evidence that ethnic inequalities exist in maternity care in the UK, but those specifically in relation to UK obstetric anaesthetic care have not been investigated before. Using routine national maternity data for England (Hospital Episode Statistics Admitted Patient Care) collected between March 2011 and February 2021, we investigated ethnic differences in obstetric anaesthetic care. Anaesthetic care was identified using OPCS classification of interventions and procedures codes. Ethnic groups were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…In England, 59% of women who give birth have had an anaesthetic procedure [38]. Improved delivery of quality intrapartum neuraxial anaesthesia and analgesia may improve postnatal outcomes, but there is a need to address the ethnic disparities in how the care is delivered [38]. Applying the principles of enhanced recovery to all caesarean births may standardise care to improve its quality [39].…”
Section: Maternity Care Has Been Slow To Introduce and Adoptmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, 59% of women who give birth have had an anaesthetic procedure [38]. Improved delivery of quality intrapartum neuraxial anaesthesia and analgesia may improve postnatal outcomes, but there is a need to address the ethnic disparities in how the care is delivered [38]. Applying the principles of enhanced recovery to all caesarean births may standardise care to improve its quality [39].…”
Section: Maternity Care Has Been Slow To Introduce and Adoptmentioning
confidence: 99%
“…Anaesthetists have an important contribution to make to improving postnatal care. In England, 59% of women who give birth have had an anaesthetic procedure [38]. Improved delivery of quality intrapartum neuraxial anaesthesia and analgesia may improve postnatal outcomes, but there is a need to address the ethnic disparities in how the care is delivered [38].…”
mentioning
confidence: 99%
“…We thank Tangel and White [1] for their interest in our paper [2]. We acknowledge that our paper unfortunately inadvertently overlooked their study of a New York State database between 2007 and 2014 which was published in 2020, although we had referenced a similar earlier study of a New York State database between 1998 and 2003 by Glance et al.…”
mentioning
confidence: 96%
“…We recently published a study of ethnic inequalities for anaesthetic care provided in maternity services in England between 2011 and 2021 2. We found that for elective caesarean birth, women from black Caribbean groups were 58% more likely to have general anaesthesia (1750 per 100 000 population) compared with white British women (1065 per 100 000 population).…”
mentioning
confidence: 99%